#Stroke. (20th April 2018) - Bundy, Jacob J; Chick, Jeffrey Forris Beecham; Hage, Anthony N; Srinivasa, Ravi N; Chaudhary, Neeraj; Srinivasa, Rajiv N; Vadlamudi, Venu; Gemmete, Joseph J
Abstract : Purpose: To describe the stroke-related Twitter network through analysis of the #Stroke hashtag. Materials and methods: 621 653 tweets containing the #Stroke hashtag were analyzed from 20 March 2012 to 31 January 2018. Twitter activity metrics, engagement, user characteristics, content analysis, and network analysis were obtained using the healthcare social media analytics platform, Symplur Signals. Results: The number of users, the number of impressions, and the number of tweets containing the #Stroke hashtag increased by an annual average of 64.9%, 87.7%, and 89.2% over the past 6 years from 20 March 2012 to 31January 2018. 69 371 tweets (11.2%) contained novel content and 48 568 tweets (7.8%) related to patient care. 181 120 (29.1%) tweets contained at least one image and 436 132 tweets (70.2%) contained links to outside resources. Stroke prevention, diabetes, and atrial fibrillation were commonly discussed topics. With regard to engagement, there were 259 438 retweets (41.7%), 366 561 mentions (59.0%), and 8549 replies (1.4%). Physicians and patients authored 52 197 (8.4%) and 41 822 (6.7%) tweets, respectively. Advocate organizations, patients, and non-healthcare individuals most frequently used the #Stroke hashtag on Twitter. Conclusion: The use of the #Stroke hashtag on Twitter has grown significantly over the 6-year study period. The majority of the discussions were held between stroke support groups and non-healthcare-related individuals, with discussion content centering around stroke prevention, stroke symptoms, associated medical conditions, and treatment options.